Broadband polarization-insensitive and wide-angle solar energy absorber based on tungsten ring-disc array. Issue 45 (12th November 2020) - Yi, Zao; Li, Jiakun; Lin, Jiangchuan; Qin, Feng; Chen, Xifang; Yao, Weitang; Liu, Zhimin; Cheng, Shubo; Wu, Pinghui; Li, Hailiang
Abstract : We find that the solar energy absorption efficiency is high under a solar spectrum at AM 1.5, and it also has polarization-independence and incidence insensitivity. Our absorber has the widest operating band compared with similar absorbers reported previously. Abstract : Nowadays, solar energy is considered one of the most clean energy sources. In addition, the data from the literature tell us that its main radiation bandwidth is approximately 295–2500 nm. In this work, we proposed a novel kind of broadband solar energy absorber based on tungsten (W) to achieve broadband absorption of solar energy. A four-layer ring-disk structure (SiO2 –SiO2 –W) is employed in our design. A finite-difference time-domain (FDTD) simulation was used to ascertain the absorption performance of the absorber. The results demonstrate that a broadband solar energy absorption was realized, the bandwidth is of 1530 nm with an absorption efficiency of more than 90%, and an absorption efficiency of 97% was achieved in this region. The absorption spectra can be tuned through changing the structural and geometric parameters. Moreover, the absorber has excellent polarization independence and can be used under incident angles from 0° to 60°. The proposed solar energy absorber is simple to fabricate, and can be used for photothermal conversion, solar energy harvesting and utilization.